A Genre Analysis of Bachelor of Arts in English’ Undergraduate Theses - Arnaiz, Runalyn O.; Colagbang, Lorlie; Inoc, Maria Regla; Torregosa, Ailene; Maxilom-Mangompit, Rowanne Marie Ramos (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2021)
Research Article (RA) is one of the most important genres that received considerable attention in genre analysis. This study sought to investigate the rhetorical structures of RA abstracts written by AB-English students of Cebu Technological University. This investigation used Hylandâ€™s (2000) framework which includes: Introduction, Purpose, Methodology, Product, and Conclusion. This paper utilizes qualitative approach where a total of fifteen abstracts were selected from Cebu Technological University. The corpus of abstracts written by AB- English students were randomly selected from the CTU graduate library. The researchers found out there were no instances of Introduction move found in the abstracts.Â The purpose move constituted the fourteen (14) abstracts in the undergraduate theses written by AB- English. Fourteen (14) studies included the method move in their research abstracts. Fourteen out of fifteen studies included the product move and thirteen (13) instances of conclusion move were found in the abstracts. The researchers concluded that the abstracts followed the commonly-applied three moves such as purpose, methodology and product. The results demonstrated that the research topics on phonology, morphology, and purposive communication were already widely-explored by the student researchers. There was a dearth of research topics related to multimodal communication, child and adolescent learners and learning principles. Therefore, this study provides implications to writing research abstracts and topics that need to be explored in the undergraduate theses writing.